INTERTWINING PROCESSES OF RECONFIGURING TRADITION: Three European Case Studies. Issue 1 (14th August 2020) - Testa, Alessandro
Abstract : This article explores the three main concepts and experiential aspects at the centre of this special issue (re-enchantment, ritualization, and heritage-making), on the empirical grounds of three different ethnographic cases from Italy, the Czech Republic, and Catalonia (Spain). The text attempts to demonstrate how re-enchantment, ritualization, and cultural heritage-making can co-exist and interact within or around the same traditional facts as complementary (or at least not mutually exclusive) processes, and also in what sense their correlation and interaction can be thought of in terms of "tradition reconfiguration". This is also done by discussing the concepts of "(re)traditionalization" and "past-presencing", and related ones, such as symbolization, mythopoiesis, popular Frazerism, and (pseudo-)religious heritage.